Using drama in café dialogue as an alternative approach in multicultural educational processes - Lyngstad, Mette Bøe (Frontiers in Education, 2025)
IntroductionThis article discuss the use of drama and storytelling in café dialogue at an adult education centre (AEC). I will present three drama workshops that were implemented as part of café dialogue and that explore the same topics as in traditional café dialogue at an AEC. Participants from different countries came together for exploration in the drama workshop, whereas the group participants in café dialogue came mostly from the same country in order to facilitate the organisation of a language host. I will also analyse and discuss the data material from the interviews as this relates to the research questions. The overall goal of this article is to explore the potential and the limitations of using drama and theatre as part of café dialogue.MethodsOur research methods are observations, logs, and interviews. Data were collected through participant and non-participant observation of three drama workshops in which several drama conventions were used. Two teachers at an AEC with a drama background led the first workshop while I observed, and I led the second workshop while one of the teachers with a drama background actively participated and wrote a log afterwards. The third workshop was led by both a teacher with a drama background and myself. After the workshops, a colleague from HVL and I conducted individual interviews with the two teachers with drama experience, a language host, and a participant in the drama workshops. In this article I analyse the interviews to gain more insight into the teachers’ and students’ experience of drama as part of café dialogue.ResultsThe students actively participated in collective creative processes and gave different topics an aesthetic form. They generated much joy and laughter in the classroom. Drama opened the way for both nonverbal and verbal communication across age and culture. Several students were reluctant at first but became more active over time thanks to the creation of a safe atmosphere and the voluntary nature of participation. The article includes many examples of drama conventions fit for use in this work, which the teacher introduces and which allow participants to take the initiative in the processes. In the drama workshops, the teachers and participants created a safe space together in which they could explore artistic expressions collectively. According to the teachers with drama experience, they too needed to be more active in these workshops. By bringing drama into café dialogue, the participants had an embodied experience and emotive fictional engagement. It seems easier to explore and play out others’ stories than one’s own. The participants experienced a sense of mastery because drama offers several possibilities they could play with and an expanded form of communication. One of the teachers found that whereas the café dialogue was structured and organised, the drama workshops were more open and made the participants more active in many ways.DiscussionIn this article, I discuss the potential and the limitations of using drama and theatre as part of café dialogue. I will interpret the drama workshop and interview material in light of theory.